Multilevel vehicle–dummy design optimization for mass and injury criteria minimization. (February 2015) - Gandikota, Imtiaz; Rais-Rohani, Masoud; DorMohammadi, Saber; Kiani, Morteza
A vehicle–dummy multidisciplinary design optimization problem is treated as a multilevel system composed of structural and occupant restraint system design elements. The vehicle-based responses and the dummy-based responses are obtained from nonlinear transient dynamic finite element simulations of full frontal impacts and side impacts. The wall thicknesses of a set of energy-absorbing components together with the occupant restraint system control parameters associated with the seat belt and the airbag are treated as design variables and used to optimize the multilevel system to minimize both the structural mass and the selected injury criteria. Each element optimization problem is modeled using the augmented Lagrangian with exponential penalty function formulation. A single-loop coordination strategy is used to solve the multilevel optimization problem. To maximize the computational efficiency, surrogate models are used to approximate the vehicle-based responses and the dummy-based responses. The results of the vehicle–dummy design problem are used to examine the computational efficiency and the accuracy of the decomposed multilevel optimization methodology.